2012
DOI: 10.1038/oby.2012.98
|View full text |Cite
|
Sign up to set email alerts
|

Diet Composition and Activity Level of at Risk and Metabolically Healthy Obese American Adults

Abstract: Obesity often clusters with other major cardiovascular disease risk factors, yet a subset of the obese appears to be protected from these risks. Two obesity phenotypes are described, 1) "metabolically healthy" obese, broadly defined as body mass index (BMI) ≥ 30 kg/m 2 and favorable levels of blood pressure, lipids, and glucose; and 2) "at risk" obese, BMI ≥ 30 with unfavorable levels of these risk factors. More than 30% of obese American adults are metabolically healthy. Diet and activity determinants of obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 44 publications
(38 reference statements)
3
19
0
Order By: Relevance
“…Consistent with the findings from the previous research [13,15,18], the association between high diet quality and metabolic health was not apparent in older age group, although in our analysis MDS was marginally significant with being more likely to be MHO phenotype in age-, gender-, and race/ethnicity-adjusted model. These findings suggest that other factors such as physical activity might be more important than diet in relation to metabolic abnormalities among older adults [36], which is supported by the fact that age-related changes in body composition, especially increase in visceral fat, may elevate the risk of cardiometabolic disease [37].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the findings from the previous research [13,15,18], the association between high diet quality and metabolic health was not apparent in older age group, although in our analysis MDS was marginally significant with being more likely to be MHO phenotype in age-, gender-, and race/ethnicity-adjusted model. These findings suggest that other factors such as physical activity might be more important than diet in relation to metabolic abnormalities among older adults [36], which is supported by the fact that age-related changes in body composition, especially increase in visceral fat, may elevate the risk of cardiometabolic disease [37].…”
Section: Discussionsupporting
confidence: 92%
“…However, these reports have been limited to MHO phenotype [13], especially without considering dietary pattern [14], or with specific age groups [15]. A few studies have reported associations in MONW phenotype in non-US population [16], but with limited generalizability [17].…”
Section: Introductionmentioning
confidence: 98%
“…This is in agreement with reports in adults (28,29). However, a recent paper demonstrated that MHO adolescents had better dietary compliance than those with MUO (30).…”
Section: Discussionsupporting
confidence: 84%
“…Hankinson et al confirmed that women with MHO slept longer than those at risk (29). We did not find any association of sleep duration with cardiometabolic outcomes.…”
Section: Discussionmentioning
confidence: 52%
“…These individuals display high levels of insulin sensitivity, favorable inflammation and lipid profiles, and a low prevalence of hypertension, and are hypothesized to be protected from, or to be at substantially lower risk of, obesity-related metabolic complications, including cardiovascular diseases, type 2 diabetes, and mortality (2)(3)(4)(5)(6)(7). There is no consensus on the definition of so-called ''healthy obesity,'' and researchers have generally used insulin sensitivity denoted by low HOMA-IR, absence of metabolic syndrome (MetS) 9 , or a combination of both, to describe the phenotype (2)(3)(4)(5). MetS is a multiplex of metabolic risk factors that includes abdominal obesity, elevated blood pressure, hyperglycemia, low HDL cholesterol, and hypertriglyceridemia (8).…”
Section: Introductionmentioning
confidence: 98%